Eco-friendly LED illumination using a modified non-inverting Cuk converter for sustainable lighting applications - B. Lakshmi Praba; Seyezhai Ramalingam (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
Light-emitting diodes (LEDs) are essential to current lighting due to their perfect control, long lifespan, great energy efficiency, and environmental friendliness. However, issues like output ripple and uneven brightness could have an impact on both visual comfort and system performance. This research presents the design and implementation of a non-inverting Cuk (NI-Cuk) converter operating in discontinuous conduction mode (DCM), integrated with a valley-fill circuit (Vfc) that reduces voltage and current (V and I) ripple and improves lifetime. The study begins with an analysis of the classic Cuk (CCuk) converter, highlighting its shortcomings, including inverted output polarity and the high current stress across the switching device. A NI-Cuk is proposed to overcome the shortcomings of CCuk, delivering a positive output with higher efficiency. Vfc offers a faster steady-state response, reduces peak loads on components, and reduces losses. To confirm that the design and hardware prototype were developed, and the results are validated with the simulated outcomes. The approach's viability is confirmed by experimental results, and a comparison of CCuk, NI-Cuk, and NI-Cuk with and without Vfc is conducted using voltage regulation, efficiency, and ripple. The results show that the suggested converter assurances are a reliable, effective, and superior power source for LED lighting applications.